Rural Settlement, Lifestyles and Social Change in the Later First Millennium AD at Flixborough, Lincolnshire Anglo-Saxon Flixborough in its Wider Context - Loveluck, Christopher (Historic England, 2007)
The quality of the overall archaeological data contained within the settlement sequence is important for both the examination of site-specific issues, and for the investigation of wider research themes and problems, facing settlement studies in England, between AD 600 and 1050. Volume 4, offers a series of thematic analyses, integrating all the forms of evidence to reconstruct the lifestyles of the inhabitants. These comprise settlement-specific aspects and wider themes. The former include relations with the surrounding landscape and region, trade and exchange, and specialist artisan activity. Whereas the wider themes consider approaches to the interpretation of settlement character, the social spectrum of its inhabitants, changing relationships between rural and emerging urban centres, and the importance of the excavated remains within contemporary studies of early medieval settlement and society in western Europe.